Internalisasi Nilai-nilai Hadis Tentang Belajar Kajian Tematik dalam Perspektif Psikologi Humanistik - Najwa Salsabillah Zalfa; Muhammad Alif (STAI Nurul Qadim, 2025)
Learning is a natural human inclination that must be developed throughout a person’s life. In Islam, the process of learning is not merely seen as an effort to acquire knowledge, but as a means to draw closer to Allah and to fully humanize individuals. The hadiths of Prophet Muhammad (peace be upon him) contain many messages emphasizing the importance of seeking knowledge, honoring teachers, respecting one another, and instilling perseverance and enthusiasm in the learning process. This study aims to explore and internalize the values contained in the Prophet’s hadiths about learning. It employs a thematic (maudhu’i) approach and connects these values with the principles of Humanistic Psychology. Using a descriptive qualitative method and thematic analysis of relevant hadiths, this research identifies values such as sincerity in learning, appreciation for the process, hope and optimism, and the motivation to reach one’s highest potential (tafaqquh fī al-dīn). The study also recommends that contemporary Islamic education should not only focus on cognitive aspects but also integrate a humanistic psychological approach grounded in the values of the hadiths. This is essential for nurturing learners who are not only intellectually intelligent but also emotionally and spiritually mature. Thus, the learning process becomes not merely a means for achieving worldly goals, but also a path toward a higher, liberating sense of life’s purpose.